I Belgi. Barbari e Poeti - Van Reeth, Louise; Nardone, Antonio (Brussel : Rond-Point des Arts vzw, 2015)
Rops, Félicien ; Spillaert, Léon ; Van de Woestyne, Gustave ; Ensor, James ; Permeke, Constant ; Van den Berghe, Frits ; Magritte, René ; Mesens, E.L.T. ; Delvaux, Paul ; Simon, Armand ; Mariën, Marcel ; D'Havé, Camille ; Alechinsky, Pierre ; Dotremont, Christian ; Charlier, Jacques ; Panamarenko ; Lennep, Jacques ; Copers, Leo ; Swennen, Walter ; Pelletti, Daniel ; Penelle, Frédéric ; Jacquet, Yannick ; Mouffe, Michel ; Broodthaers, Marcel ; Messieurs Delmotte ; Buggenhout, Peter ; Duhem, Paul ; Tassini, Pascal ; Fabre, Jan ; Bernier, Pascal ; Vanmechelen, Koen ; De Bruyckere, Berlinde ; Muyle, Johan ; Gloup Gloup ; Delvoye, Wim ; Ferretti, Mario ; Filippini, Alessandro ; Moerman, Jean-Luc ; Van Duynen, Phil ; Solheid, Vincent ; Van Roy, Patrick ; Hell'o Monsters
I Belgi. Barbari e Poeti, MACRO, Roma, 15.05.2015 - 13.09.2015 / Vanderborght, Brussel, 02.10.2015 - 03.01.2016
boek